A Critical Appraisal of Stolorow's Criticism of Kohut's Concept of the Self and His Contextualization of Heidegger's Notion of Authenticity plus the Possibility of an Intersubjective Self Psychology. Issue 4 (2nd October 2021) - Riker, John Hanwell
ABSTRACT: In this paper I want to contest claims made by Robert Stolorow that Kohut's notion of the self is a reified concept that seriously distorts our understanding of human experience, that his own theory of phenomenological contextualism is an adequate way to explore the psychological depths of human subjectivity, and that Heidegger's theory of authentic individuality can be adequately translated into his intersubjective contextualism. My aim is to salvage the notion of self and authentic individuality from collapsing into what I see as an overzealous contextualism, establish the importance of doing theory that explores psychological and metaphysical structures underlying experience, and show how self psychology and intersubjectivity theory might be fused into a comprehensive way to investigate the human psyche. It is the dialectical tension between being an independent center of initiative and perception and being thoroughly contextualized that is the truth of the self and I believe that this is Kohut's basic position.